2013
DOI: 10.1371/journal.pone.0082252
|View full text |Cite
|
Sign up to set email alerts
|

On the Encoding of Proteins for Disordered Regions Prediction

Abstract: Disordered regions, i.e., regions of proteins that do not adopt a stable three-dimensional structure, have been shown to play various and critical roles in many biological processes. Predicting and understanding their formation is therefore a key sub-problem of protein structure and function inference. A wide range of machine learning approaches have been developed to automatically predict disordered regions of proteins. One key factor of the success of these methods is the way in which protein information is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Table 4 illustrates the AUC value of 10 cross validation batch datasets of Disorder723 with settings of different combinations of feature classes. Not surprisingly, the most contributing feature class is evolutionary information, which confirms that it is the conservation profile that makes the order/disorder regions different [ 18 ]. The second important feature class is the structural information class which is based on predicted secondary structure and solvent accessibility.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Table 4 illustrates the AUC value of 10 cross validation batch datasets of Disorder723 with settings of different combinations of feature classes. Not surprisingly, the most contributing feature class is evolutionary information, which confirms that it is the conservation profile that makes the order/disorder regions different [ 18 ]. The second important feature class is the structural information class which is based on predicted secondary structure and solvent accessibility.…”
Section: Resultsmentioning
confidence: 98%
“…In short, it has been demonstrated that charged and hydrophilic residues, such as P, E, S, Q and K are more likely to be in disordered states, whereas neutral and hydrophobic residues, such as C, W, I, Y, F, L, M and H, are order-promoting residues [ 2 ]. It has also been suggested that evolutionary conservation largely determines order/disorder states [ 18 ]. Besides these amino acid and evolution related features, we need to find additional relevant and/or complementary features that could contribute to the order/disorder prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1672 proteins in the test set were divided into five bins of size 214, 452, 508, 233, and 265 proteins, in increasing helix/beta content. In general, increased coil content tends to align with increased disorder and associated flexibility in a protein 50,101 , so our test set separation corresponds to an increasing degree of disorder. Figure 2 captures the increasing helix and beta content and corresponding decreasing coil content across the five sampled proteins, one from each test bin.…”
Section: Resultsmentioning
confidence: 99%
“…These excellent predictors performed better in CASP (Critical Assessment of techniques for protein Structure Prediction) comparing with previous methods. Becker et al also presented a predictor [ 40 ], which was competitive in terms of accuracy with respect to the state-of-the-art.…”
Section: Introductionmentioning
confidence: 99%